Multi-Band Propagation and Radio Channel Characterization in Street Canyon Scenarios for 5G and beyond - Dupleich, Diego; Müeller, Robert; Landmann, Markus; Shinwasusin, Ek Amorn; Saito, Kentaro; Takada, Jun Ichi; Luo, Jian; Thomä, Reiner; Del Galdo, Giovanni (IEEE Access, 2019)
Radio access at mm-waves has been subject of intensive research in the latest years. However, within the initial deployment of 5G, mm-waves are still relegated and there is a generalized idea that the mm-wave channel for radio access, in comparison to the sub-6 GHz channel, is not only sparse but also troublesome for outdoor applications. In the present paper we introduce simultaneous multi-band measurements comparing the sub-6 GHz with the mm-waves channel at 30 GHz and 60 GHz in street canyon scenarios using the same measurement equipment in Germany and Japan. An analysis on the propagation and radio channel characteristics shows that the mm-waves channel offers similar opportunities as the sub-6 GHz. Consequently, the challenge relies on the design of an adequate radio interface matching the channel characteristics. In that regard, aspects as the location of clusters and spatial consistency gain importance within geometry-based stochastic channel models (GBSCMs). The analysis of the large-scale parameters (LSPs) has shown a large influence of the geometry of the scenario on the channel, encouraging the introduction of deterministic modelling components within GBSCMs targeting these scenarios.
CRIS-Team Scopus Importer:2025-11-10
Keywords: 5G; mm-waves; Multi-band measurements; quasi-deterministic channel modelling; street canyon; sub-6 GHz